Respondiendo a un desafío pendiente en Geografía. El enfoque de género visto desde España - García Ramón, María Dolors (Geographicalia, 2016)
In an article signed by myself just fifteen years ago I was advocating the need of not excluding from our research in human geography half of the humankind, thereby arguing that the introduction of the gender approach was an unavoidable task. Nowdays it could be asserted that gender studies have been fully integrated in international Geography althoug at very different rates in different regions of the world. The present article tries to present first, the recent developments and new trends at the internacional level since the 1990's and, second, to present a survey of the scietific procduction on the field in Spain since the gender approached was introduced.
Keywords: Gender Geography; feminist Geography; Spanish Geography; postmodersnim; feminist inethodologies.